Aprendizaje Basado en Competencias para la enseñanza-aprendizaje de la asignatura de Matemáticas en los estudiantes de Bachillerato General Unificado. - Pineda Labanda, Cristhian Enrique (2024)
Competency-Based Learning (CBL) is an active methodology, student-centered and focused on the assessment of competencies, to validate efficient performance in given contexts. In this regard, the research focused on determining the importance of Competency-Based Learning on teaching and learning Mathematics in the General Unified High School. It is an exploratory study based on a qualitative approach and certain quantitative characteristics; the data gathering was carried out from a variety of sources, using techniques such as documentary review and signing, supported by instruments, such as the search log and bibliographic and content sheets. The findings show that CBL facilitates the development of mathematical skills and meaningful learning, thus improving academic performance; moreover, empirical studies reported improvements in problem solving and reasoning skills. In this way, it is concluded that CBL is effective in the teaching-learning process of Mathematics, as it allows to contextualize knowledges and evaluate competences. Keywords: methodology, skills, contexts, curriculum, meaningful learning, efficient performance.